Excavatolide C has oxidative-stress-dependent antiproliferative and apoptotic effects against breast cancer cells - Jun-Ping Shiau; Che-Wei Yang; Wangta Liu; Szu-Yin Yu; Chia-Hung Yen; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (BMC Cancer)
Abstract Background Triple negative breast cancer (TNBC) shows a poor response to targeted therapy drugs for non-triple-negative breast cancer (non-TNBC). Developing anticancer drugs that are effective for both TNBC and non-TNBC cells is necessary. The marine coral Briareum excavatum-derived excavatolide C (EXCC) exhibits anti-bladder cancer cell proliferation. However, the anti-breast cancer properties and drug safety of are unclear. Methods This study aimed to evaluate the antiproliferative effect and mechanisms (oxidative stress, DNA damage, and apoptosis) caused by EXCC on TNBC and non-TNBC cells in parallel with normal cells. Results EXCC demonstrated higher antiproliferative effects in various breast cancer cell lines (MDA-MB-231, Hs578t, MDA-MB-468, and MCF7) than in normal breast cell lines (H184B5F5/M10; M10) as detected in a 48 h ATP assay. MDA-MB-231 and MCF7 were chosen as representative TNBC and non-TNBC cells, respectively, to clarify the underlying molecular mechanisms. EXCC highly upregulated reactive oxygen species and mitochondrial superoxide, reduced the mitochondrial membrane potential, and downregulated glutathione in breast cancer compared with normal cells. These EXCC-triggered antiproliferative and oxidative stress changes were attenuated by the ROS inhibitor N-acetylcysteine (NAC). Consistently, in breast cancer cells, EXCC triggered subG1 accumulation, apoptosis, caspase activation, and DNA damage (γH2AX and 8-hydroxy-2’-deoxyguanosine), all of which were alleviated by NAC. Conclusion Overall, the antiproliferative effects and molecular mechanisms caused by EXCC in breast cancer treatment depend on oxidative stress. Without cytotoxicity to normal cells, EXCC is a potential antiproliferative marine natural product for TNBC and non-TNBC cells.